Comparative screening of in-vitro free radical scavenging, anti-inflammatory and anti-haemolytic activities from non-polar solvent extracts of Pterocarpus marsupium - Aruna LH,; Sanjeevkumar CB,; Amarvani PK,; Ramesh L Londonkar, (International Journal of Phytomedicine, 2017)
Pterocarpus marsupium is widely used as ‘Rasayana’ in ayurvedic system for curing several medical ailments. In view of this, petroleum ether and chloroform extracts of Pterocarpus marsupium bark was scrutinized to unfold free radical scavenging by measuring their capability for scavenging DPPH radical, ABTS, phosphomolybdenum assay as well as reducing power capacity assessment and anti- inflammatory activity by inhibition of protein denaturation. Additionally, RBC’S were also used to explore the potentiality of Pterocarpus marsupium different extracts to shield RBC in oxidative stress condition. Chloroform extract showed an effective pharmacological activity in all assays when compared with petroleum ether extract and their respective standards. This reveals the use of Pterocarpus marsupium as a potent source of antioxidant, anti-inflammatory, anti-haemolytic agent and would provide an ample opportunity for further investigation. Isolation of active compounds from this plant responsible for producing such bioactivities is under process.